Has differentiated instructions gone ‘awry’ in online teaching and learning? - Idrus, Faizah; Zainal Asri, Nurafini; Baharom, Nurin Najihah (Academy Publication, 2021)
Differentiated Instruction (DI) is a classroom strategy that helps teachers to cater their teachings to students with different abilities and learning needs. The issue here is whether DI is still relevant in the online teaching and learning amidst the COVID-19 pandemic. Thus, the aim of this paper is to explore selected ESL teachers’ practices of differentiated instructions in their online classes. It also seeks to examine challenges these teachers withstand while implementing DI in their online classrooms. A qualitative design employing the semi-structured interviews and teachers’ reflection notes are used as data collection instruments. A total of six English language teachers from three selected schools in Malaysia took part in this investigation. Thematic analysis following Braun and Clarke (2006) is applied. The findings revealed that environmental strain, resources constraint and students’ and parents’ attitudes are the main challenges in DI while teaching in an online platform.